Teknologi Tradisional Orang Alune dalam Menggunakan Bahan Pewarna Alam pada Jenis-Jenis Anyaman Bambu di Desa Riring Kecamatan Taniwel Kabupaten Seram Bagian Barat - Gressilia Lumaderine; Hamid Dokolamo (Program Studi Pendidikan Geografi FKIP Universitas Pattimura, 2025)
In the context of sustainable education within island regions, the integration of local ecological values and transformational leadership practices remains an important yet underexplored field of inquiry. This study focuses on the preservation of natural dyeing technology among the Alune community in Riring Village as a representation of local wisdom–based eco-pedagogy. The objective is to analyze the structure of indigenous knowledge, its transmission system, and its contribution to developing a model of transformational eco-leadership. Employing a qualitative case study design, data were collected through in-depth interviews, participatory observation, and document analysis conducted over six months. The findings reveal that traditional dyeing serves not only as a cultural and economic activity but also as an ecological learning process that cultivates moral responsibility, environmental spirituality, and intergenerational collaboration. This study extends transformational eco-leadership theory by integrating cultural and spiritual values into sustainable educational practice